Simulation and Experimental Verification of a HB-Type Vernier Motor - Thejel, R. H.; Hairik, H. A.; Alwan, M. A. (Engineering, Technology & Applied Science Research, 2013)
Direct drive motors are used as actuators in numerous applications in which they must rotate at low speeds with high torque and low torque ripple. Various types of vernier motors have been studied recently. The HB type vernier motor is one of them. Its rotor structure is the same as in a HB type stepping motor but has a field winding at the rotor and has multiphase windings in the stator. In the present work, a Matlab simulation of a HB type vernier motor is presented. To validate the motor results and response, the authors fabricated the motor and implemented its drive circuit. The motor was tested for different load conditions. Experimental results are found identical to simulation results and it is also shown that the motor has low torque ripple.